The Role of Law of the Republic of Indonesia Number 12 of 2022 concerning Sexual Violence Crimes in Handling Cases of Gender-Based Violence in Indonesia - Zuwanda, Zulkham Sadat; Triyantoro, Andri (West Science Law and Human Rights, 2024)
This paper examines the application of Law Number 12 of 2022 on the Crime of Sexual Violence in addressing cases of gender-based violence (GBV) within Indonesia’s creative economy. Using a juridical analysis approach, the study explores the effectiveness of the law in protecting victims, prosecuting offenders, and preventing future incidents of sexual violence in a sector characterized by informal employment and unique workplace dynamics. Case studies of sexual violence incidents in the creative economy reveal challenges in reporting, barriers in legal processes, and the critical role of industry stakeholders in mitigating or enabling GBV. While the law offers comprehensive protections, including victim support and criminal sanctions, its effective implementation requires enhanced law enforcement training, workplace safety policies, and accessible reporting mechanisms. The study concludes with recommendations to strengthen the application of Law Number 12 of 2022, ensuring greater protection for creative industry workers from gender-based violence.